THE COMPARISON OF RESIN-BASED COMPOSITES PHYSICAL PROPERTIES BETWEEN BULK-FILL TECHNIQUE AND INCREMENTAL TECHNIQUE - Rahmi Khairani Aulia (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACT:Composite resins are currently the most popular restorative material in dentistry. This is due to good aesthetics and maximum conservation ability. Behind these advantages, there are disbenefits of composite resin materials, such as polymerization shrinkage, which can lead to restoration failure. Various attempts have been investigated to reduce the shrinkage incidence of composite resins, one of which is the technique of placing the restorative material into the cavity. The restoration filling technique is recognized as a significant factor in shrinkage stress. By using a special filling technique, the polymerization shrinkage damage stress can be reduced. There are several techniques in performing composite resin fillings, including bulk and incremental techniques. These techniques have their respective advantages and disadvantages. The aim of this literature review was to compare the physical properties of composite resin restorations with bulk filling and incremental techniques. Physical properties that being studied include polymerization shrinkage, stress shrinkage, degree of conversion, bonding strength, water resorption, color stability, and temperature increase. Comparing the two techniques, composite resin with incremental filling technique has superior physical properties compared to bulk technique. From the comparison of the two techniques, the composite resin with incremental filling technique has superior physical properties compared to the bulk technique, especially in higher conversion which causes lower shrinkage stress. This situation makes the incremental technique provide better bond strength, water resorption, color stability, and lower temperature rise.Keywords: Bulk, Composite Resin, Incremental,  Physical Properties, Restoration, Restoration Technique